2009
DOI: 10.1111/j.1365-2052.2009.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping a quantitative trait locus on horse chromosome 2 associated with radiological signs of navicular disease in Hanoverian warmblood horses

Abstract: Navicular disease or podotrochlosis is one of the main causes of progressive forelimb lameness in warmblood horses. The objective of this study was to refine a quantitative trait locus on horse chromosome 2 for radiological alterations in the contour of the navicular bone (RAC) in Hanoverian warmblood horses. Genotyping was performed in 192 Hanoverian warmblood horses from 17 paternal half-sib groups. The marker set was extended to 58 informative microsatellites including nine newly developed microsatellites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A number of potential changes can result from one or many factors. On the basis of molecular studies it was concluded that there are genetic conditions making an individual horse prone to navicular disease, however, genes that could code for this defect are numerous LOPES et al 2009). These studies have determined specific regions on chromosomes with nucleotide polymorphisms responsible for dysfunction which may contribute to the development of navicular syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A number of potential changes can result from one or many factors. On the basis of molecular studies it was concluded that there are genetic conditions making an individual horse prone to navicular disease, however, genes that could code for this defect are numerous LOPES et al 2009). These studies have determined specific regions on chromosomes with nucleotide polymorphisms responsible for dysfunction which may contribute to the development of navicular syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach takes advantage of historical recombinants to refine the location of QTL. For example, haplotype analysis utilizes historical recombinants to fine‐map the QTL of interest (Lopes et al. 2009).…”
Section: Introductionmentioning
confidence: 99%